DATA TRANSPARENCY AND INFORMATION SHARING: CORONAVIRUS PREVENTION PROBLEMS IN INDONESIA - Sofia Al Farizi; Bagus Nuari Harmawan (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2020)
Background: Information and data of coronavirus outbreak from central government shared publicly was lacking. Such the lack of information and data has several negative impacts, such as confusion about the information experienced by local governments in accessing positive case data at the beginning of the pandemic and the red zone of the spread of the corona virus, "panic buying" by the community, and confusion on finding accurate data source to respond to the corona pandemic.Aim: This study analyzed the Indonesian Government's attitude in providing information and data transparency of the latest coronavirus outbreak to the public in Indonesia.Method: This study was qualitative research with a content analysis approach. Some information in this analysis was retrieved from COVID-19 official websites of the Indonesian Government and other Indonesian governmental institutions. To deepen the analysis, this study also featured South Korea and Singapore official websites. Other information was also obtained from mass media, social media, and policy briefs.Results: Coronavirus data transparency in Indonesia was still insufficient as seen from the information and data on the official COVID-19 website. Since the first coronavirus case was announced on March 2nd to March 17nd, 2020, the Government also did not provide comprehensive data on the outbreak through official speeches. The process of case tracking was also not carried out openly. Some case tracking innovations were also released late and massive coronavirus tests for tracking cases also did not run optimally. Information and data delivered to the public through policy speeches were inconsistent and closed in nature.Conclusion: Insufficient data transparency and information sharing can be seen from the availability of partial data on website, not optimal case tracking process, and inconsistent and instransparant information conveyed through policy messages. Keywords: Coronavirus, data transparency, information, prevention.